A tradition-historical analysis of Psalm 55 - Human, Dirk J. (Verbum et ecclesia, 1997)
A tradition-historical analysis of Psalm 55. The text of Psalm 55 will be remembered for its musical setting by Felix Mendelsohn and others and also for the fact that it is one of the most difficult psalms to analyse. A tradition-historical analysis of the traditions and history of the poem confinns the unique and independent character of the text. The content of the psalm is characterised by vague allusions to well-known salvational and historical traditions as well as the psalm's characteristic fonnulations. Themes from the primeval history and desert wanderings of Israel are identifiable. Moreover, tenninology with a socalled priestly background, reflect the psalm's cultic setting and junction, while a theme from the Zion tradition is also evident. Prophetic language is evident in both legal concepts and tenninology which expresses guilt. Relationships with wisdom texts are also evident. This article is an attempt to identify and detennine the function of the above-mentioned traditionsgeschichtliche themes in order to gain a better understanding of the text.